1998
DOI: 10.1021/jf980687v
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Content of Flavonol Glycosides in Green Beans and Their Fate during Processing

Abstract: Four varieties of green bean (Phaseolus vulgaris) were analyzed for flavonol composition and content. Two flavonol conjugates, not previously reported in green bean, were found in three of the varieties. These are quercetin 3-O-(2G-β-d-xylopyranosylrutinoside) (1), (1.0−2.0 μg/g of fresh weight) and the corresponding kaempferol analogue (2) (0.3−0.7 μg/g). The major flavonol component in all of the varieties was quercetin 3-O-glucuronopyranoside (3) (3.5−15.1 μg/g) with lesser amounts of quercetin 3-O-rutinosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 20 publications
5
66
0
1
Order By: Relevance
“…Boiling has been shown to induce flavonol losses of 20% and 40% in onions and asparagus, respectively. 21 Price et al 22 reported that canning did not result in chemical breakdown of flavonol glycosides but that leaching into cooking water was significant and depended on the conjugate. Cooking by boiling or frying of onions 23 led to a 25% loss of flavonol glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Boiling has been shown to induce flavonol losses of 20% and 40% in onions and asparagus, respectively. 21 Price et al 22 reported that canning did not result in chemical breakdown of flavonol glycosides but that leaching into cooking water was significant and depended on the conjugate. Cooking by boiling or frying of onions 23 led to a 25% loss of flavonol glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Standards of quercetin glucuronides and of quercetin glucosides were either synthesized or extracted from plants as described previously (Price et al, 1998;Day et al, 2001). All polyphenolic standards were Ͼ97% pure; the identities, including position of attachment of the conjugate, have been determined using chemical synthesis and NMR (O'Leary et al, 2001).…”
mentioning
confidence: 99%
“…Three compounds (1-3) were isolated from the 70% MeOH extract by repeated column chromatography on MCI gel CHP20P, Sephadex LH20 and silica gel. The structures of these compounds were identified as amentoflavone [11], kaempferol 3-O--Dglucopyranoside [12] and kaempferol 3-O--Dglucuronopyranoside [13] (Figure 1) on the basis of NMR spectral data and comparison with reported values in literatures.…”
Section: Resultsmentioning
confidence: 99%